2016
DOI: 10.1002/chem.201601592
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Syntheses of Lignin Models: An Efficient Synthesis of β‐O‐4 Dimers and Trimers by Using the Evans Chiral Auxiliary

Abstract: We describe an efficient five-step, enantioselective synthesis of (R,R)- and (S,S)-lignin dimer models possessing a β-O-4 linkage, by using the Evans chiral aldol reaction as a key step. Mitsunobu inversion of the (R,R)- or (S,S)-isomers generates the corresponding (R,S)- and (S,R)-diastereomers. We further extend this approach to the enantioselective synthesis of a lignin trimer model. These lignin models are synthesized with excellent ee (>99 %) and high overall yields. The lignin dimer models can be scaled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…33 However, our screen on auxiliaries found that 4c had a slightly better diastereoselectivity than 4e ( see Figure S2 and Table S2 in SI). Thus, 4c was selected as the chiral auxiliary for subsequent preparations.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…33 However, our screen on auxiliaries found that 4c had a slightly better diastereoselectivity than 4e ( see Figure S2 and Table S2 in SI). Thus, 4c was selected as the chiral auxiliary for subsequent preparations.…”
mentioning
confidence: 94%
“…Thus, the stereospecific anti -dilignols were obtained in just four steps with an overall 42% yield, which was a significant improvement over the other asymmetric methods reported so far. 32, 33 …”
mentioning
confidence: 99%
“…Later, cinnamic acid is transformed into three types of lignols including p -coumaryl, coniferyl and sinapyl alcohol, which are the precursors for lignin [48] Acetylation of coniferyl alcohol produces coniferyl acetate, which is converted into eugenol, which in turn has been reported to have an anti-cancer effect through increased apoptosis [49, 50]. In this study, the proposed lignin structure consists of two coniferyl acetate linking with an ether bond, namely a β-O-4 linkage [51]. A previous study has shown that lignin fractions obtained from the conventional fractionation of Acacia nilotica extract had a half inhibitory concentration (IC50) on human breast cancer cell line (MCF-7) lower than 100 μg/mL [52] This is in accordance with our findings with an IC50 on CCA cell lines lower than 63 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, model compounds are often employed to simplify product identification and reaction condition optimization. For example, dimeric models that consist of either two simple phenols, or one phenol and one lignol via C−C or C−O linkages (Scheme , i and ii), have been extensively applied to study oxidation, reduction and modification of lignin . Despite their widespread use, those dimers remain compromised in terms of structural feature comparing to those found in authentic lignin largely due to the lack of proper C3 side chain units.…”
Section: Methodsmentioning
confidence: 99%